1987
DOI: 10.2307/3576902
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis and Cytotoxicity in Human Epithelial Cells by Far- and Near-Ultraviolet Radiations: Action Spectra

Abstract: Action spectra were determined for cell killing and mutation by monochromatic ultraviolet and visible radiations (254-434 nm) in cultured human epithelial P3 cells. Cell killing was more efficient following radiation at the shorter wavelengths (254-434 nm) than at longer wavelengths (365-434 nm). At 254 nm, for example, a fluence of 11 Jm-2 gave 37% cell survival, while at 365 nm, 17 X 10(5) Jm-2 gave equivalent survival. At 434 nm little killing was observed with fluences up to 3 X 10(6) Jm-2. Mutant inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(57 citation statements)
references
References 45 publications
2
54
0
1
Order By: Relevance
“…Forty-eight hours after plating, the medium was replaced with serum-free medium. MTT assays were performed at four time points (1,3,6, and 9 h). At each time point, cell viability was measured using the MTT assay as described previously (15).…”
Section: Mtt Assay For Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight hours after plating, the medium was replaced with serum-free medium. MTT assays were performed at four time points (1,3,6, and 9 h). At each time point, cell viability was measured using the MTT assay as described previously (15).…”
Section: Mtt Assay For Cell Viabilitymentioning
confidence: 99%
“…Most studies have concentrated on the role of UV irradiation due to its high energy, photoreactivity, wide range of biological chromophores, specific cellular responses, and association with pathologies such as skin melanoma and cataract (1)(2)(3)(4). However, the role of visible light has been less extensively investigated, even though studies have demonstrated that visible light can induce cellular dysfunction and cell death both in vitro and in vivo (1)(2)(3)(5)(6)(7). The blue region (400 -500 nm) of the visible spectrum is likely to be particularly important because it has a relatively high energy, can penetrate tissue(s), and is associated with the occurrence of malignant melanoma in animal models (6,7).…”
mentioning
confidence: 99%
“…Reports of mutation induction by broad-band sources fail to exclude the contribution of shorter wavelengths and results using monochromatic radiation at various UVA wavelengths vary with die wavelength and cell type employed (5)(6)(7). For example the results of our own study (5) did not demonstrate mutation induction at the hypoxanthine guanine phosphoribosyl transferase (HGPRT*) locus by radiation at a wavelength of 365 nm in cultured human lymphoblastoid cells whereas such radiation does appear to be mutagenic in a human teratocarcinoma cell line (6) and in cultured human fibroblasts (7).…”
Section: Introductionmentioning
confidence: 99%
“…First, UVA irradiation (ÏŸ320 nm) is far less mutagenic than UVB (290 -320 nm) or UVC (Ïœ290 nm) irradiation (31,32), and is supported by the safe use of UVA in human clinical studies (33,34). Second, although different cells exhibit different sensitivities to UVA damage, it is far less variable than cell type sensitivities to UVB and UVC damage (31,35,36). The results of the present work are consistent with this expectation, demonstrating a modest range of sensitivities (3.2-fold) among seven diverse cell types.…”
Section: Figmentioning
confidence: 99%